Competing phases in the superconducting state of La2-xSrxCuO4: Temperature- and magnetic-field-dependent quasiparticle relaxation measurements - Bianchi, G; Chen, C; Nohara, M; Takagi, H; Ryan, J (2005)
We present femtosecond time-resolved measurements of the quasiparticle dynamics in La2-xSrxCuO4 (LSCO) as a function of the temperature and applied magnetic field. Temperature-dependent data correlate with independent equilibrium measurements of superfluid density and charge dynamics. At low temperature, the induced reflectivity transient is established in a two-step process. We propose that this behavior results from the coexistence of two energy scales in the superconducting state of LSCO: the superconducting (SC) gap and a partial gap at higher energy that decrease with increasing doping and vanish in overdoped material. Measurements under applied magnetic field indicate that, in the SC state, the response is remarkably sensitive to a c-axis field. We show that this is due to the development of nonsuperconducting regions of size ∼130 surrounding vortex cores. The data show that a partial gap persists in these regions, suggesting that this gap is associated with electronic correlations competing with superconductivity. © 2005 The American Physical Society.